Oral Clindamycin and Metronidazole in the treatment of bacterial vaginosis in pregnant black women: Comparison of efficacy and pregnancy outcome - CC, Ijeoma; TK, Nyengidiki; G, Bassey; RN, Ogu; JO, Alegbeleye; KT, Wariso (Clinical Journal of Obstetrics and Gynecology, 2020)
Bacterial vaginosis (BV) is associated with adverse pregnancy outcomes with various treatment options. Objective: To compare the efficacy and effect on pregnancy outcome of Metronidazole and Clindamycin in women with bacterial vaginosis in Port Harcourt, Nigeria. Methodology: Randomized controlled study of 136 pregnant women diagnosed with BV at the University of Port Harcourt Teaching Hospital. A structured proforma was used to obtain socio-demographic characteristics and other relevant data. Treatment was with either oral Metronidazole or oral Clindamycin for seven days. A secondary test and evaluation of the effect on adverse pregnancy outcomes were determined. Data analysis was done using the SPSS statistical package version 22.0 Results: BV prevalence was 23%, with similar cure rates with both medications. The failure rates of clindamycin and metronidazole were 10.4% and 13% respectively (p = 0.639). The mean gestational age at delivery in the metronidazole treated group was 38.67 weeks ± 1.69 compared to 38.68 weeks ± 1.64 in the oral clindamycin group (p = 0.96). Pre-labour rupture of membranes and preterm delivery rates with both medications were similar (p = 0.73; OR 1.3; 95% CI 0.3-4.9) and (p = 0.73; OR 1.3; 95% CI 0.3-4.9) respectively. Conclusion: Both medications have comparable efficacy and similar pregnancy outcomes in the treatment of bacterial vaginosis in low-risk asymptomatic pregnant Nigerian women and thus can be used interchangeably.